2010
DOI: 10.1093/toxsci/kfq289
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Japanese Quail (Coturnix japonica), Common Pheasant (Phasianus colchicus), and White Leghorn Chicken (Gallus gallus domesticus) Embryos to In Ovo Exposure to TCDD, PeCDF, and TCDF

Abstract: Egg injection studies were performed to confirm a proposed model of relative sensitivity of birds to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). In this model, species are classified as belonging to one of three categories of sensitivity based on amino acid substitutions in the ligand-binding domain of the aryl hydrocarbon receptor. Embryo lethality and relative potencies of 2,3,7,8-tetrachlorodibenzofuran (TCDF) and 2,3,4,7,8-pentachlorodibenzofuran (PeCDF) were compared with TCDD for Japanese quail (Coturnix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 25 publications
4
63
0
Order By: Relevance
“…Quail were more resistant than chicken or pheasant to embryotoxicity caused by TCDD, 2,3,4,7,8‐PeCDF, or TCDF after injection of eggs into the air sac in a range of 0.22–37 pmol/g egg with for TCDD‐induced mortality a NOAEL of 1,824 pg/g egg and an LD 50 of 9,700 pg/g. In contrast to chicken, the order of chemical potency was PeCDF > TCDF > TCDD (Cohen‐Barnhouse et al., ). However, with other chronic toxicity endpoints, such as deformities, body and organ weights and histopathology, the comparisons were not as clear as with embryo mortality and could not be used to derive a dose response (Cohen‐Barnhouse et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Quail were more resistant than chicken or pheasant to embryotoxicity caused by TCDD, 2,3,4,7,8‐PeCDF, or TCDF after injection of eggs into the air sac in a range of 0.22–37 pmol/g egg with for TCDD‐induced mortality a NOAEL of 1,824 pg/g egg and an LD 50 of 9,700 pg/g. In contrast to chicken, the order of chemical potency was PeCDF > TCDF > TCDD (Cohen‐Barnhouse et al., ). However, with other chronic toxicity endpoints, such as deformities, body and organ weights and histopathology, the comparisons were not as clear as with embryo mortality and could not be used to derive a dose response (Cohen‐Barnhouse et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Recent studies have found that TCDD, TCDF, and 2,3,4,7,8-PeCDF may not be equipotent in birds, as was concluded by the most recent assessment by the WHO [23,[72][73][74]. Based on the results of egg injection studies in Japanese quail [74], a species that falls into the same broad category of sensitivity to dioxin-like compounds as GBH, TCDF and 2,3,4,7,8-PeCDF were found to be twofold and sixfold more potent, respectively, than TCDD at causing embryo lethality. By applying these relative potencies to the concentrations observed in GBH eggs collected in the current study, concentrations expressed as DF-TEQ increased approximately threefold.…”
Section: Uncertainty Assessmentmentioning
confidence: 90%
“…Unlike feeding trials, they allow a rapid and cost-effective means of determining toxicity of individual compounds or mixtures. Furthermore, a number of egg injection studies have effectively established the impacts of hydrophilic and hydrophobic vehicles and compounds, including PCBs, dioxins, PBDEs, dibenzofurans, perfluorooctane sulfonate, and methyl mercury [45,51,52,[54][55][56][57][58][69][70][71][72][73][74][75]. These studies have contributed to our understanding of toxicity profiles and measurement endpoints, and have given us data useful in directly estimating the egg concentrations in wild birds and the modes/timing of maternal transfer [10,63].…”
Section: Discussionmentioning
confidence: 99%